Distribution and genetic types of loess landslides in China - Peng, Jianbing; Wang, Shaokai; Wang, Qiyao; Zhuang, Jianqi; Huang, Weiliang; Zhu, Xinghua; Leng, Yanqiu; Ma, Penghui (Journal of Asian earth sciences, 2019)
[Display omitted] •An inventory of 14,544 loess landslide cases was established.•Tectonics is the primary factor causing clustering of loess landslides on the Loess Plateau of China.•Loess landslides are classified into six genetic types. In this study, 14,544 loess landslides collected from the Loess Plateau of China are used to reveal their distribution and origins. Main factors considered include landslide density, regional tectonics, soil properties, geomorphic structure, rainfall distribution, seismic activity, and human activity. Based on these factors, the Loess Plateau is divided into eight zones with high possibilities of landslides that are classified into six genetic types. The first genetic type of clustering distribution of loess landslides is related to several main regional active faults. The second type is related to broken pieces of loess geomorphic structures. The third type is considered to be due to unloading of the geomorphic peripheral slope that can cause the internal structural plane to open and thus controls the prototype and scale of the loess landslide. Change of hydrogeological conditions in the slope softens the loess pedestal and the slippery layer, forming a softening zone and thus controlling the shear crack and slip model of the fourth type of loess landslides. The fifth type is due to seismic activities that can generate additional stress to the Earth's surface and landform slopes, causing the opening of joints and seismic liquefaction. The last type of landslides is caused by human activities by changing the geological structure, hydrogeological conditions, and the inner stress balance of slopes.